Massive Hematemesis from a Splenic Artery Pseudoaneurysm Presenting Two Years after Penetrating Trauma - Geraldine Abbey-Mensah; Michael M. Herskowitz; James Walsh; Robert F. Leonardo (Case Reports in Radiology)
Splenic artery pseudoaneurysms (PSA) are rare entities and far less common than true aneurysms of the splenic artery. The most common etiology is pancreatitis, recurrent either in the setting of chronic pancreatitis or as an episode of acute pancreatitis. Less common causes include trauma, peptic ulcer disease, or iatrogenic causes. Almost all of the trauma-related case reports have been due to blunt trauma. We believe this to be the first reported case of a splenic artery PSA presenting with massive hematemesis at a significant time frame after penetrating trauma. Successful transcatheter treatment was performed and alternative techniques are also discussed.